Ett svenskt landskap i Australien : svenska kyrkan i Melbourne - Lundh, Christian (SLU/Dept. of Landscape Architecture, Planning and Management (from 130101), 2006)
As a Swedish landscape architecture student living in Australia for five years, I have often wondered if my memories and my associations with the landscape and the nature in Sweden, are the same as other Swedish people living in Melbourne. Most of the Swedish people who live here in Melbourne remember and associate Sweden's nature and landscape with where they grew up or where they used to live. The plants that most of the Swedish people I asked missed from Sweden were associated to special feelings or activities. The general type of landscape people remember from Sweden is that of a landscape covered in forests, which you can walk freely through. With these memories as a foundation and with inspiration from the Swedish landscape architect Thorbjörn Anderson's way of creating places, by letting a few strong changes play against the existing elements,2 but also with consideration of the climate and the severe shortage of water that is current in Melbourne, will I create a design concept for the garden surrounding the Swedish Church in Melbourne. A design concept that will generate memories and associations to Swedish landscapes.